The modernization of NBA offenses and why Small Ball is here to stay - Fenichel, A. (The Analyst, 2021)
The small-ball era in the NBA isn`t actually about how tall your center is. What`s it actually about? Here`s an update on where the league`s offensive revolution stands in 2021.